Antibacterial Activity of Calendula Officinalis Flowers In Vitro - M.N. Hamad; H.J. Mohammed; M.A. Merdaw (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Flower  samples of Calendula officinalis were collected from the gardens of the college of Pharmacy in Baghdad city  to examine their antibacterial activity .The effect of ethanol crude extract of petals and reproductive parts of flowers in different concentrations were obtained and bioassayed in vitro for its bioactivity to inhibit the growth of eight types of bacteria .The extracts of petals  part were clearly superior for all bacteria especially the bacteria Pseudomonas aeruginosa (inhibition zone was 25mm in the concentration 100mg/ml) from gram negative bacteria, and Staphylococcus aureus (inhibition zone was 14mm in the concentration 50mg/ml) from gram positive bacteria, while the extracts of reproductive parts were less effective than petals part. These results confirm the antibacterial activity of Calendula officinalis flowers and support the traditional use of the plant in the therapy of bacterial infection